KEMAMPUAN MENULIS ANAK DOWN SYNDROM USIA 8 TAHUN DI SLB KARYA IBU PALEMBANG - Iren Intania; Rafilla Rameyzah; Alini Rahmadani; Nina Tri Lestari; Mutiara Suffa Aisyah; Nia Ramadhani; Yuni Dwi Suryani; Dara Zulaiha (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to describe the writing skills and strategies of teachers in learning children with Down syndrome. The method used is descriptive qualitative with data sources of teachers and students. This study was conducted at SLB Karya Ibu Palembang with observation, interview and documentation data collection techniques. Finally, it was analyzed with data reduction, data presentation and conclusions. The results show that at SLB Karya Ibu Palembang there are several children with Down syndrome. Of course, children's writing skills are hampered, such as children who can already hold a pencil and can thicken the letter "S", only the letters that are thickened are not finished, only in the upper curve and children often erase. Therefore, it requires learning strategies and approaches. SLB Karya Ibu Palembang teachers use individual learning strategies and empathy approaches. By understanding children's needs and their respective potentials, in accordance with individual learning strategies, teachers can create a learning environment that supports writing development. These learning objectives are designed to suit children's abilities, by targeting mastery of simpler competencies, such as learning to write the alphabet A-Z and thicken letters using picture media. An empathy approach is also applied so that students feel comfortable and supported in an inclusive environment. In terms of development, the findings show positive progress in students, despite limitations caused by Down syndrome.